2008
DOI: 10.1103/physrevlett.101.137003
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Coexistence of the Pseudogap and Superconducting Quasiparticles inBi2Sr2CaCu2O8+yby Time-Resolved Optica

Abstract: We report the ultrafast optical response of quasiparticles (QPs) in both the pseudogap (PG) and superconducting (SC) states of an underdoped Bi2Sr2CaCu2O8 + y (Bi2212) single crystal measured with the time-resolved pump-probe technique. At a probe energy variant planck's over omegapr = 1.55 eV, it is found that the reflectivity change DeltaR/R changes its sign at exactly Tc, which allows the direct separation of the charge dynamics of PG and SC QPs. Further systematic investigations indicate that the transient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
80
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 36 publications
14
80
0
Order By: Relevance
“…They then reach equilibrium by high-frequency phonon decay. A theoretical framework for analyzing the transient data has being established on the basis of comprehensive and systematic experiments on various superconductors 5,[8][9][10][11] involving BCS-type, 12 cuprates, 6,7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] Fe-based superconductors, 27 and other related compounds. 28 In the cuprates, the distinction of the QP dynamics between SC and PG has been realized by the characteristics of each dynamics, such as relaxation time, temperature dependence, [12][13][14][16][17][18][19] or dependence on the external fields.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They then reach equilibrium by high-frequency phonon decay. A theoretical framework for analyzing the transient data has being established on the basis of comprehensive and systematic experiments on various superconductors 5,[8][9][10][11] involving BCS-type, 12 cuprates, 6,7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] Fe-based superconductors, 27 and other related compounds. 28 In the cuprates, the distinction of the QP dynamics between SC and PG has been realized by the characteristics of each dynamics, such as relaxation time, temperature dependence, [12][13][14][16][17][18][19] or dependence on the external fields.…”
Section: Introductionmentioning
confidence: 99%
“…20 The differences in transition probability and matrix elements for optical probe transitions also provide a possibility to selectively enhance the QP dynamics detection of SC/PG, which allows us to analyze each dynamics individually. 17,22 In our previous paper, we selectively isolated the transient dynamics associated with SC and PG QPs in UD-Bi2212 by changing the probe beam energy and polarization. 22 We also showed that two distinct components can be detected simultaneously below T c .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,11,25,26 This fundamental discrepancy was attributed to the dependence of ΔR/R on several factors including laser power, 15,23 wavelength, 25,27 polarization, 25,28 and repetition rate 24,29 . Furthermore, in a recent effort to uncover the transient optical signatures of the pseudogap (PG) phase, [11][12][13][14]28,[30][31][32] and elucidate a possible relationship between the PG state and SC state in OD YBCO [31][32] , the PG phase was either identified as a weak transient feature 11,30 or found to be completely absent from the spectra. 9,19,25,26 Here, we report on a new procedure to obtain the definitive ultrafast optical RT model.…”
mentioning
confidence: 99%
“…them [1][2][3][4][5][6]. Recently, in the cuprate superconductor Bi 2 Sr 2 CaCu 2 O 8+δ the detailed research on the probe-polarization dependence of the carrier dynamics has revealed that the observed polarization anisotropy arises from spontaneous symmetry breaking (SB) in the superconducting and pseudogap phases [7].…”
mentioning
confidence: 99%